Effects of Vanadium on Rice Growth and Vanadium Accumulation in Rice Tissues - Boonhong Chongkid; Naramol Vachirapattama; Yaowapha Jirakiattikul (Agriculture and Natural Resources, 2007)
The experiment on effects of vanadium on rice growth in hydroponic culture with the Mckeehen’s nutrient solution formulae was conducted during September 5 to January 3, 2005 at the Department of Agricultural Technology, Thammasat University, Rangsit Campus, Thailand. Vanadium of 80 mg/l caused the lowest stem height, stem diameter, fresh and dried stem weights, and fresh and dried root weights of 84.21 cm., 1.98 cm., 24.44 and 9.61 g, and 20.59 and 1.47 g, respectively. Without Vanadium, a tendency to give the longest root of 48.85 cm, the highest number of panicles per hill of 11.00, the highest number of seeds per panicle of 222.18, the highest weight of seeds per hill of 58.55 g, and the highest 100-seed weight of 2.40 g were obtained. The two vanadium concentrations of 40 and 80 mg/l, however, caused death to the rice plant before the flowering stage. The vanadium concentrations were found in the root > leafy stem > seed, respectively.